The influence of physical education on harmonious development of personality - Stas'uk R.M; Vostozka I.F; Osipova I.L (Kharkov National Pedagogical University, 2010)
Engaged in a physical culture and sport create terms for comprehensive, harmonious development of personality. The large variety of motive actions allows to decide the difficult complex of tasks of teaching and education of rising generation. Different maintenance and orientation of physical exercises is instrumental in harmonization of personality. Exercises are directed on development of basic high-quality sides of motive activity. Also on education morally-volitional qualities and perfection of aesthetically beautiful presentations. Exercises are instrumental in harmonization of personality. A choice of physical exercises of predetermines is scalene complex education of man.